德州市区域经济发展决策定位分析 ： 实施外向型发展战略 = Strategic analysis of economic development in Dezhou city : an outward-looking development strategy - 李安义 Li, An Yi. (2008)
The paper analyses the macroeconomic economic environment affecting regional economy. It describes the gains from trade and investment from domestic and foreign sources.